Prolonged rectal shedding of SARS-CoV-2 in a 22-day-old-neonate: a case report - Julie Niemann Holm-Jacobsen; Julia Helena Vonasek; Søren Hagstrøm; Mette Line Donneborg; Suzette Sørensen (BMC, 2021)
Abstract Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes the novel coronavirus disease 2019 (COVID-19), which is characterized by a diverse clinical picture. Children are often asymptomatic or experience mild symptoms and have a milder disease course compared to adults. Rectal shedding of SARS-CoV-2 has been observed in both adults and children, suggesting the fecal-oral route as a potential route of transmission. However, only a few studies have investigated this in neonates. We present a neonate with a mild disease course and prolonged rectal SARS-CoV-2 shedding. Case presentation A 22-day old neonate was admitted to the hospital with tachycardia and a family history of COVID-19. The boy later tested positive for COVID-19. His heart rate normalized overnight without intervention , but a grade 1/6 heart murmur on the left side of the sternum was found. After excluding signs of heart failure, the boy was discharged in a habitual state after three days of admission. During his admission, he was enrolled in a clinical study examining the rectal shedding of SARS-CoV-2. He was positive for SARS-CoV-2 in his pharyngeal swabs for 11 days after initial diagnosis and remained positive in his rectal swabs for 45 days. Thereby, the boy remained positive in his rectal swabs for 29 days after his first negative pharyngeal swab. Conclusions The presented case shows that neonates with a mild disease course can shed SARS-CoV-2 in the intestines for 45 days. In the current case, it was not possible to determine if fecal-oral transfer to the family occurred, and more research is needed to establish the potential risk of the fecal-oral transmission route.